ANALISIS PENGARUH KEPATUHAN MEMBAYAR ZAKAT TERHADAP KEBERKAHAN - Juliana Nasution (Universitas Islam Negeri Sumatera Utara, 2017)
This research was aimed to find out how big the direct and indirect influence of faith, reward, altruism, organization's response to compliance variable and their impacts toward blessings of muzakkis’ wealth. The sample in this research is muzakki of profession zakah paid in Dompet Dhuafa Waspada. The research method used is a quantitative approach, by using path analysis with MSI as a helping program, SPSS version 16 and LISREL 8.8 (student). Dominant factors affecting blessing to pay zakah were organization and compliance. The dominant factors that influenced blessing were compliance and reward. The form of blessing were the most widely experienced by respondents after obediently to pay zakah is smoothness and the provision addition. And then, selective to their revenues, control of needs a life, family harmony, perseverance worship, treasures preserved from theft, and inner peace.